Inertia of Original Country’s CSR Impact on Corporate Financial and Market Performance : Evidence of Multinational Corporations in China - Bo, Wu; Hamrila, Abdul Latip; Mahani, Mohammad; Sharizal, Hashim (Scientific Research Publishing, 2023)
After entering the host country, multinational corporations often adopt a series of localization strategies in order to overcome the maladjustment caused by the inertia of some corporations when operating in the host country. This paper selects the corporate social responsibility inertia, which is most easily ignored in the corporate organizational inertia, as the analysis point to explore the impact of corporate social responsibility inertia on corporate performance and market. This combination of stakeholder theory and corporate social responsibility: structural inertia, environmental protection inertia and moral inertia. And use fixed effects mode in econometrics to empirically test the market performance data of multinational corporations in China from 2017 to 2022. The research finds that the structural inertia of corporate social responsibility negatively affects corporate performance. The moral inertia and environmental protection inertia of corporate social responsibility effects on corporation market performance is shown as a Kuznets curve. Through the improvement of localization strategy, corporations can overcome the inertia of the original country.